The Influence of the Problem Based Learning (PBL) Cooperative Learning Model on Improving the Learning Outcomes of Class XI SMA Dharma Utama Students - M, Marnoko; Berutu, Riska Sartika Dewi (Journal of Innovation in Research, Education and Culture (JIREC), 2024)
This research was carried out with the aim of finding out the effect of the Problem Bassed Learning model on students' economic learning outcomes. The problem in this research is the low economic learning outcomes of class Data collection used to determine the desired results is using questionnaires and tests. Where previously it had been tested for validity, reliability and hypothesis testing, so that from the research results it was obtained that the average score of students achieved the expected learning objectives using the problem based learning model. This research hypothesis was tested using the SPSS program with a significance level of α=0.05, so that a calculated t value of 6.669 was obtained with a t table of 1.701. So the results of the Ha hypothesis are accepted and Ho is rejected. Thus, it can be concluded that there is an influence of the problem-based learning model on student learning outcomes in the material for calculating national income in class XI SMA Dharma Utama, Serdang Bedagai. Keywords: Learning Model, Problem Bassed Learning, Learning Outcomes